2003
DOI: 10.1556/aagr.51.2003.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous application of manures and fertilizers on productivity of cotton-sorghum rotation

Abstract: Field experiments were conducted from 1985 through 2001 on medium deep vertisol to determine the effect of the continuous application of manure and fertilizers on a two-year cotton-sorghum rotation. The results indicate that the response to N was greatest during the initial years, while after five to six rotation cycles the yield levels declined to the zero level in the N and NK plots. The application of P along with N prevented the decline in seed cotton and sorghum grain yields. The effect was more pronounce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…More number of sympodial branches contributes to higher seed cotton production. Application of FYM with chemical fertilizer considerably increased number of branches plant -1 , which may probably increase crop yield (Blaise et al, 2003(Blaise et al, , 2005. Furthermore, it was reported that combined application of PM with synthetic NP fertilizer also increased the number of branches plant -1 (Venugopalan and Tarhalkar, 2003;Joshi et al, 2016).…”
Section: Plant Height At Maturity (Cm)mentioning
confidence: 99%
See 3 more Smart Citations
“…More number of sympodial branches contributes to higher seed cotton production. Application of FYM with chemical fertilizer considerably increased number of branches plant -1 , which may probably increase crop yield (Blaise et al, 2003(Blaise et al, , 2005. Furthermore, it was reported that combined application of PM with synthetic NP fertilizer also increased the number of branches plant -1 (Venugopalan and Tarhalkar, 2003;Joshi et al, 2016).…”
Section: Plant Height At Maturity (Cm)mentioning
confidence: 99%
“…Furthermore, it was reported that combined application of PM with synthetic NP fertilizer also increased the number of branches plant -1 (Venugopalan and Tarhalkar, 2003;Joshi et al, 2016). (Blaise et al, 2003(Blaise et al, , 2005Nehra et al, 2006). These results are in concurrence with (Venugopalan and Tarhalkar, 2003), found that integrated nutrient management for cotton crop ensure better boll formation and development, thereby increase seed cotton yield.…”
Section: Plant Height At Maturity (Cm)mentioning
confidence: 99%
See 2 more Smart Citations
“…There should be an alternative approach which reduces heavy reliance on both organic and inorganic fertilizers. Combined application of organic and inorganic fertilizers increase agricultural productivity, improve soil fertility and decrease environmental pollution (Erkossa & Teklewold, 2009;Mugwe et al, 2007;Wakene et al, 2007;Blaise et al, 2003;Corbeels et al, 2000). However, this approach has not been yet widely tested in arid and semiarid parts of Ethiopia.…”
Section: Soil Fertility Managementmentioning
confidence: 99%